Performance of Maize Following Groundnut Varieties at Different Densities - Lilongwe University of Agriculture and Natural Resources (International Food Policy Research Institute, 2021)
This dataset is generated from maize response trials (legume/maize rotation system) that were conducted in Linthipe EPA, Dedza district, and Ntubwi EPA in Machinga district in Malawi, 2019/2020 cropping season. In the previous season, certifies and recycled seed of different varieties of groundnut were grown. In the current season, maize was planted as a test crop.